Benthic and Planktonic Microalgae Community in Probolinggo Beach: Biodiversity - Arsad, Sulastri; Sihombing, Rut Suharni P; Mahmudi, Mohammad; Luthfi, Oktiyas Muzaky; Safitri, Ikha; Pratiwi, Fika Dewi (Journal of Aquaculture and Fish Health, 2024)
Microalgae, micro-sized plant organisms, play a crucial role in aquatic ecosystems. While many microalgae inhabit substrates or the bottom of water bodies, several types are planktonic. This study aimed to identify the types and abundance of microalgae in both sediment and water column habitats, as well as to analyse the environmental factors influencing their abundance. The research encompasses observations of water quality factors, microalgae abundance, relative abundance, diversity index, evenness index, and dominance index. Statistical analyses were using non-metric multidimensional scaling (NMDS) and Canonical Correspondence Analysis (CCA). The study was conducted in May-June 2022, with bi-weekly sampling at three points within each location for two months. Microalgae identified in the coastal area of Probolinggo belong to the Bacillariophyceae, Cyanophyceae, and Chlorophyceae classes. The highest microalgae abundance in sediment habitat was 58,472 ind/cm2, while in the water column was 4,118 ind/l. Diversity, evenness, and dominance indices in both sediment and water column habitats ranged from 1.93 to 2.61, 0.88 to 0.98, and 0.09 to 0.10, respectively. NMDS and CCA analyses indicate a graphical representation of the Bacillariophyceae class, demonstrating its prevalence across all sites.